The influence of training load on postural control and countermovement jump responses in rugby union. Issue 4 (2nd October 2019) - Troester, Jordan C.; Jasmin, Jason G.; Duffield, Rob
ABSTRACT: Purpose: This study investigated responses of single-leg balance and landing and countermovement jump (CMJ) following rugby union training and the specific components of training load associated with test decrement.Methods: Twenty-seven professional rugby union players performed CMJ, single-leg balance and landing tests on a 1000 Hz force plate at the beginning and end of training days. Training load was described by session RPE, Banister's TRIMP, GPS total distance, high-speed running distance (>5.5 m s −1 ), relative speed and body load.Results: CMJ eccentric rate of force development (EccRFD) demonstrated moderate impairment post-training (ES ± 90%CL = −0.79 ± 0.29, MBI = almost certainly ). CMJ height (−0.21 ± 0.16, possible ), concentric impulse (ConIMP) (−0.35 ± 0.17, likely ) and single-leg balance sway velocity on the non-dominant leg (0.30 ± 0.26, possible ) were also impaired. Regression analyses identified the strongest relationship between sRPE and impaired ConIMP (r = −0.68 ± 21, β = −0.68) whilst other load measures explained 27–50% of the variance in balance and CMJ changes.Conclusions: CMJ variables representing altered movement strategy (EccRFD and IMP) may be useful for assessing acute neuromuscular fatigue in rugby union, though single-leg balance sway velocity may be an alternative when maximal tests are impractical.